Peran Guru Akidah Akhlak dalam Mengembangkan Program P5 pada Peserta Didik di MTsN 6 Kediri - Subakir; Rahmawati , Septiya Dwi (IIQ An Nur Yogyakarta, 2025)
Education plays a crucial role in shaping students’ character, competence, and spirituality. However, the learning process often encounters various obstacles, such as limited teacher competence, inadequate facilities, and weak collaboration among educational stakeholders. These challenges hinder the achievement of optimal learning outcomes. This study employed a qualitative case study approach using observation, interviews, and documentation. Data analysis was conducted using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing.The findings revealed that the main obstacle lies in teachers’ limited pedagogical skills, resulting in monotonous teaching methods and low student engagement. Inadequate infrastructure and the underutilization of digital media also negatively affected the quality of learning. Furthermore, weak collaboration between teachers and school leaders hampered the implementation of innovative programs, including the Pancasila Student Profile Strengthening Project (P5), which emphasizes character development, collaboration, and student independence. These challenges can be addressed through continuous professional development for teachers, stronger school leadership support, and more intensive stakeholder collaboration.In conclusion, overcoming these inhibiting factors requires not only individual teacher improvement but also systemic strategies that ensure high-quality learning and the optimal implementation of P5. Thus, education can produce students who are not only academically competent but also embody the values of Pancasila in their daily lives.